EVALUASI IMPLEMENTASI STANDAR PELAYANAN MINIMAL PADA UNIT GAWAT DARURAT RS PABATU PTPN IV KABUPATEN SERDANG BEDAGAI - Sabrina Indra (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
Improving service and quality in the emergency department does not only have implications for clinical aspects but must also rely on safety and service delivery aspects. Hospital management must develop a program aimed at improving the process of emergency service units, which refers to the Minister of Health Minimum Service Standards No. 47 of 2018. This research uses a descriptive observational study design with a qualitative approach, which aims to obtain successful implementation of Minimum Service Standards in Emergency departments. The main informants in the study were those in charge of the emergency room, doctors on duty, and nurses. The Pabatu Hospital Emergency Installation already has good readiness in terms of human resources, facilities, and infrastructure, as well as medical materials to support emergency services. In the service variable, the specialist doctor's service response time of > 10 minutes is still below the specified standard of < 5 minutes with an achievement rate of 33.3%. This is due to the distance from the domicile surgeon who is quite far from the hospital, so it takes a slower travel time. The facilities and infrastructure variables have met the standards specified with a requirement level of 100%, except for the surgery room and stretcher storage room. From the results of the study, it was also obtained that the variable readiness of medical materials for the Emergency Room at Pabatu Hospital had met the standards specified with a 100% conformity level for each indicator. The Pabatu Hospital Emergency Room has also implemented the LASA and FIFO systems in managing drug supply. In the human resource variable at the Emergency Room at Pabatu Hospital, its only met a conformity level of 12.5% for the nurse indicator with emergency training certification. This is due to the management policy which will provide regular training. The observations found an increase in the number of visits by 50-70% on certain days which had an impact on a significant increase in the workload of emergency room workers.